The Relationship between Political Parties and New Media In the Kurdistan Region: The New Generation Movement During the October 2024 Elections as a Model - fatah ڕێبین (Zanco Journal of Law and Politics گۆڤاری زانكۆ بۆ یاساو رامیاری, 2025)
Politics and the media in general can complement each other and there is an interchangeable relationship between them, especially the new media and its tools play a major role on political power and political characters. Political parties and movements, as a complementary face of the media, resort to new media, and are forced to do this, because they cannot ignore the influence and role of this type of media, especially in the era of technological advancement A strong and complementary exchange relationship between political parties and the new media. In the Kurdistan Region, political parties, especially the Nawa-i-Nuw Movement, which was born in the era of technological advancement and the appearance of smart phones, has certainly fallen under the influence of this type of media Therefore, there is a strong relationship between political parties and the new media, which is fully reflected in the political activities of the Nawa-i-Nuw Movement. The new media also opened up a large and extensive market for the Nawa-i-Nuw movement, because this movement; Through this media, it was able to reach more people in the Kurdistan Region, especially the first person page of the movement, a form or kind of online political participation was more active, by individuals, because the emergence of this form of political participation Request via comments. Therefore, the Nawa-i-Nuw movement has a strong relationship with the new media, and some consider this party to be the product of the birth of the new media and social networks.